The Role Of Digital Literacy In Improving Students’ Competence In Digital Era - Muhammad Iqbal Murtadho; Rizqa Yuhda Rohmah; Zahrotul Jamilah; Muhamad Furqon (AL-WIJDÃN Journal of Islamic Education Studies, 2023)
In the current digital age, students are required to possess high level of digital literacy. Digital literacy refers to an individuals’ ability to effectively find, evaluate, and use information throughdigital technology. The aim of this study is to explore the role of digital literacy in enhancing students’ competencies in the digital age. The methodology used in this study is by collecting data from class observations, interviews with teachers, and surveys to students and parents. The result of this study indicates that digital literacy affects students’ abilities in leraning, collaborating, and facing challenges in the digital age. The implications of the study suggest that digital literacy is crucial in preparing students to face challenges in the digital age, such as resulting on better academic performance, increasing students’ interest in learning, and preparing students’ readiness to face future challenges.  Keywords: Digital Age, Digital Literacy, Students’ Competency